Promoted MoxCy‐based Catalysts for the CO2 Oxidative Dehydrogenation of Ethane. Issue 13 (27th April 2022) - Marquart, Wijnand; Raseale, Shaine; Claeys, Michael; Fischer, Nico
Abstract: The CO2 oxidative dehydrogenation reaction has the potential to play a role in the advancement of CO2 ‐utilizing catalytic reactions, co‐activating CO2 and short‐chained alkanes. Transition metal carbides are promising catalysts for this reaction, in particular Mox Cy, however catalytic stability is a major challenge. In this study, the addition of a promoter (Fe, K, Ni or Pt) has shown to significantly influence the crystal structure of the carbide system as well as the acid‐base characteristics. K promotion decreased the number of acid sites, limiting ethane activation and the removal of the oxygen surface species formed in CO2 activation. The catalysts deactivate due to oxidation to MoOx . Fe decreased the initial activity, but it increased the stability of the oxygen surface species, which enhanced the stability of the catalyst and ethylene selectivity to outperform the unpromoted sample. Oxidation of the carbide and carbon deposition during the reaction could not be prevented. Ni promotion increases the number of basic sites, enhancing the CO2 activation, shown by the highest activity obtained during the reverse water‐gas‐shift experiments. At higher CO2 content in the feed the dry‐reforming reaction becomes the dominant reaction pathway. Pt suppressed the dry‐reforming reaction, but instead increased the direct dehydrogenation activity, accompanied by a high degree of carbon deposition. No oxidation to MoOx was observed at a stoichiometric CO2 to C2 H6 feed ratio. Abstract : CO2 ‐assisted oxidative dehydrogenation : the promoter (Fe, K, Ni or Pt) significantly alters the crystallographic properties, acid/base characteristics and catalytic performance of the Mox Cy ‐based catalyst. The reaction pathway is greatly affected upon co‐feeding of H2, H2 O or increased CO2 content. The Figure Shows an indication of the dominating pathway for each catalyst (location of star), it's C2 H6 conversion (size of star) at the various feed gas compositions.